2004
DOI: 10.1073/pnas.0400322101
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental role of inferior olive connexin 36 in muscle coherence during tremor

Abstract: Inferior olive (IO) neurons are electrically coupled by cytosolic pores formed by the neuron-specific connexin 36 (Cx36). Electrical coupling in the IO figures prominently in current views about brain control of movement. However, a role for Cx36 in movement has been questioned and not definitively demonstrated. Previous reports have shown that embryonic deletion of the Cx36 gene resulted in almost complete loss of cytosolic and electrical coupling in the IO without an obvious deficit in movement, possibly due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…In contrast, reports of nonzero-phase difference have only been reported anecdotally in vivo (22,24,34) and never been studied systematically. Nonetheless, kinematic studies in harmaline-treated rats suggest that IO coupling is required to maintain tight, nonzero-phase differences between muscle pairs, further supporting our results (35). The mechanism of phase-difference maintenance still requires elucidation, but probably relies on direct or indirect coupling between oscillating IO neurons.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, reports of nonzero-phase difference have only been reported anecdotally in vivo (22,24,34) and never been studied systematically. Nonetheless, kinematic studies in harmaline-treated rats suggest that IO coupling is required to maintain tight, nonzero-phase differences between muscle pairs, further supporting our results (35). The mechanism of phase-difference maintenance still requires elucidation, but probably relies on direct or indirect coupling between oscillating IO neurons.…”
Section: Discussionsupporting
confidence: 76%
“…In rodents, I T was inhibited acutely by ethanol and long-chain aliphatic alcohols (19,20), whereas I h was augmented by ethanol (21). Recent studies demonstrated that the tremor mediated by the IO requires Ca V 3.1 T-type calcium channels (22,23) and is synchronized by gap junctions (24).Here, we demonstrate that primate IO neurons are oscillatory pacemakers and that chronic intoxication for over 1 y in monkeys is associated with potentiated Ca V 3.1 channel function within the IO and acute withdrawal tremor. Our experiments indicate that sustained (30-d) abstinence following chronic intoxication does not return the brain to the preethanol state but rather is associated with a below-normal decrease in rebound excitability in IO neurons and therefore reveals a form of bidirectional plasticity of pacemaking excitability.…”
mentioning
confidence: 69%
“…In rodents, I T was inhibited acutely by ethanol and long-chain aliphatic alcohols (19,20), whereas I h was augmented by ethanol (21). Recent studies demonstrated that the tremor mediated by the IO requires Ca V 3.1 T-type calcium channels (22,23) and is synchronized by gap junctions (24).…”
mentioning
confidence: 99%
“…As such, then, the main coherence control parameter is the mutual temporal shifts among sequences of action potentials innervating different muscles. Recent experimental work indicates that such a temporal signal mechanism is provided by the sequence of oscillatory events in the olivo-cerebellar system (7). The possibility that a ''universal control system,'' based on olivo-cerebellar physiology, may be implemented in analog hardware electronic chips has been proposed (8).…”
mentioning
confidence: 99%
“…Electrophysiological studies have indicated that such motor intention patterns require proper olivocerebellar system function (1)(2)(3)(4). And, in particular, sets of time-coherent inferior olive (IO) action potentials reach given motor neuron pools by means of the cerebellar nuclei (1,(5)(6)(7). To provide the required synchrony of muscle activation, the IO signals must be temporally coherent at the final motor path regardless of the distance between the activated muscle groups.…”
mentioning
confidence: 99%